The Mechanisms of Maize Resistance to Fusarium verticillioides by Comprehensive Analysis of RNA-seq Data - Wang, Yanping; Zhou, Zijian; Gao, Jingyang; Wu, Yabin; Xia, Zongliang; Zhang, Huiyong; Wu, Jianyu (Frontiers in Plant Science, 2016)
Fusarium verticillioides is the most commonly reported fungal species responsible for ear rot of maize which substantially reduces grain yield. It also results in a substantial accumulation of mycotoxins that give rise to toxic response when ingested by animals and humans. For inefficient control by chemical and agronomic measures, it thus becomes more desirable to select more resistant varieties. However, the molecular mechanisms underlying the infection process remain poorly understood, which hampers the application of quantitative resistance in breeding programs. Here, we reveal the disease-resistance mechanism of the maize inbred line of BT-1 which displays high resistance to ear rot using RNA high throughput sequencing. By analyzing RNA-seq data from the BT-1 kernels before and after F. verticillioides inoculation, we found that transcript levels of genes associated with key pathways are dramatically changed compared with the control treatment. Differential gene expression in ear rot resistant and susceptible maize was confirmed by RNA microarray and qRT-PCR analyses. Further investigation suggests that the small heat shock protein family, some secondary metabolites, and the signaling pathways of abscisic acid, jasmonic acid, or salicylic acids (SA) may be involved in the pathogen-associated molecular pattern-triggered immunity against F. verticillioides. These data will not only provide new insights into the molecular resistant mechanisms against fungi invading, but may also result in the identification of key molecular factors associated with ear rot resistance in maize.